2015
DOI: 10.1111/jav.00705
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kleptoparasite and host numbers on the risk of food‐stealing in an avian assemblage

Abstract: 18Kleptoparasitism involves the theft of resources such as food items from one individual by for all months grouped. Successful, kleptoparasitism was more likely to occur when the total 34 number of all kleptoparasites per host was greater. Across the entire winter study period, 35oystercatcher foraging attempts that resulted in kleptoparasitism were associated with a mean 36 number of kleptoparasites per host that was more than double that for foraging attempts that 37 ended in the oystercatcher successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
10
0
3
Order By: Relevance
“…Hartlaub's gulls generally target different prey from terns (Ryan 1987) and therefore may benefit by exploiting terns when the payoffs from self-foraging decline (Brockmann and Barnard 1979;Ens et al 1990;Flower et al 2013). Associating with gulls may entail greater costs when the ratio of kleptoparasitic individuals to hosts increases (Wood et al 2015). Consistent with this prediction, data in Table S1 suggest that Hartlaub's gull may steal a larger proportion of tern prey when relative tern numbers decline, though this pattern is unclear and is confounded by between year effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hartlaub's gulls generally target different prey from terns (Ryan 1987) and therefore may benefit by exploiting terns when the payoffs from self-foraging decline (Brockmann and Barnard 1979;Ens et al 1990;Flower et al 2013). Associating with gulls may entail greater costs when the ratio of kleptoparasitic individuals to hosts increases (Wood et al 2015). Consistent with this prediction, data in Table S1 suggest that Hartlaub's gull may steal a larger proportion of tern prey when relative tern numbers decline, though this pattern is unclear and is confounded by between year effects.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing nest failure, or nest abandonment by terns under such circumstances might aggravate per capita kleptoparasitism on remaining breeders, potentially threatening colony persistence (Oro et al 1996;St. Clair et al 2001;Blackburn et al2009, Wood et al 2015, with profound consequences at the population level. However, this appears to be an unlikely threat to greater crested terns on Robben Island at present, as the species' breeding numbers have increased over the last few decades in this region (Crawford 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2). Aggressive behaviours among birds typically become more common as the density of individuals within a habitat increases (Metcalfe and Furness 1987;Wood et al 2015). It is possible that Bewick's Swans would show increasing durations of aggression with rising swan numbers if observations could be made over a greater range of swan numbers; although with ongoing declines in Bewick's Swan numbers at wintering sites in the UK (Beekman et al 2019), obtaining such data may prove challenging.…”
Section: Table 4 Comparison Of Models Of the Time Spent In Aggressive Interactions Between Swansmentioning
confidence: 99%
“…As Peiman and Robinson (2010) reported that aggression is more likely between individuals with the greatest overlap in resource use, our first hypothesis (hereafter termed the 'conspecific hypothesis') was that swans would devote more time to intraspecific aggression compared with interspecific aggression. Aggressive behaviours among birds typically become more common as the density of individuals within a habitat increases (Metcalfe and Furness 1987;Wood et al 2015), thus our second hypothesis (hereafter termed the 'density hypothesis') was that swans would spend more time engaged in aggressive interactions when present in higher density flocks. Finally, we expected that as winter progressed, a dominance hierarchy would establish among individual swans within their flock, and so reduce further aggression; indeed, Scott (1981) reported that the frequency of fights between Bewick's Swans declined progressively over winter months.…”
Section: Introductionmentioning
confidence: 99%
“…Oystercatchers feeding on mussels need to open the shells in order to swallow the soft flesh of the prey (Goss-Custard and Dit Durell 1988), which requires relatively long handling times. As a result, the birds are sensitive to interference and allowing other individuals to steal prey (kleptoparasitism)(Ens and Goss-Custard 1984;Wood et al 2015). Within avian assemblages, gulls are known to steal food items from several wading bird species(Amat and Aguilera 1990;Ens et al 1990;…”
mentioning
confidence: 99%